2019
DOI: 10.1186/s13000-019-0835-z
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative analysis of confocal microscopy on fresh breast core needle biopsies and conventional histology

Abstract: Background Evaluation of core needle biopsies (CNB) is a standard procedure for the diagnosis of breast cancer. However, tissue processing and image preparation is a time- consuming procedure and instant on-site availability of high-quality images could substantially improve the efficacy of the diagnostic procedure. Conventional microscopic methods, such as frozen section analysis (FSA) for detection of malignant cells still have clear disadvantages. In the present study, we tested a confocal micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Preservation of tissue integrity of acridine orange-stained and imaged tissue for conventional histopathologic examination has been demonstrated by other investigators, with findings similar to ours. [31][32][33] In addition, optimal preservation of acridine orange-stained and imaged tissue for subsequent immunohistochemistry and genomic studies has been established recently. 32,34 The imaged CNBs can potentially be used for immunohistochemical analysis and genomic testing after formalin fixation and routine processing.…”
Section: Discussionmentioning
confidence: 99%
“…Preservation of tissue integrity of acridine orange-stained and imaged tissue for conventional histopathologic examination has been demonstrated by other investigators, with findings similar to ours. [31][32][33] In addition, optimal preservation of acridine orange-stained and imaged tissue for subsequent immunohistochemistry and genomic studies has been established recently. 32,34 The imaged CNBs can potentially be used for immunohistochemical analysis and genomic testing after formalin fixation and routine processing.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of high-quality cell blocks cannot be overemphasized in the today’s era of personalized cancer treatment, particularly when concurrent tissue procurement based on core needle biopsy is either not performed or is suboptimal or nondiagnostic for determining the status of various biomarkers for targeted therapy of the tumor. The integrity of the procured material exposed to fluorescent dyes such as acridine orange for subsequent immunohistochemical and molecular testing has been demonstrated in previous reports with use of surgical pathology material 21 , 22 . With use of technological advancements, the quality and pseudocoloring of the digital CM images that could be obtained from cytology specimens in our study, specifically the resolution and digital staining, can be further improved to appear much better than what was achieved in our study.…”
Section: Discussionmentioning
confidence: 85%
“…As our center receives frequent breast specimen for analysis, we chose breast tissue for our study comparing FCM to standard frozen sections to evaluate whether the procedure can be performed in a satisfactorily fashion and in a time frame comparable to frozen sections. A study by Elfgen et al showed promising results for comparing breast specimen biopsies to H&E images utilising a different FCM platform [ 10 ].…”
Section: Introductionmentioning
confidence: 99%